2017
DOI: 10.1371/journal.pone.0169794
|View full text |Cite
|
Sign up to set email alerts
|

The First Chloroplast Genome Sequence of Boswellia sacra, a Resin-Producing Plant in Oman

Abstract: Boswellia sacra (Burseraceae), a keystone endemic species, is famous for the production of fragrant oleo-gum resin. However, the genetic make-up especially the genomic information about chloroplast is still unknown. Here, we described for the first time the chloroplast (cp) genome of B. sacra. The complete cp sequence revealed a circular genome of 160,543 bp size with 37.61% GC content. The cp genome is a typical quadripartite chloroplast structure with inverted repeats (IRs 26,763 bp) separated by small singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
5
15
0
Order By: Relevance
“…The collinear blocks of the genes including ribosomal RNA, tRNA, and protein coding genes revealed that all the seven genomes were relatively conserved with no gene rearrangement ( Figure 3 ). Some other studies have revealed homology in genome organization and no gene rearrangements, thus our findings support their conclusions [ 31 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 92%
“…The collinear blocks of the genes including ribosomal RNA, tRNA, and protein coding genes revealed that all the seven genomes were relatively conserved with no gene rearrangement ( Figure 3 ). Some other studies have revealed homology in genome organization and no gene rearrangements, thus our findings support their conclusions [ 31 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 92%
“…In our study 101 and 119 total SSRs were found in E. larica and E. smithii respectively, which is higher than the Euphorbiaceae family members [32]. However, it is similar to the previously reported B. sacra cp genome [42]. Among the dinucleotide SSRs, AT was found to be the most abundant in the sequenced and compared cp genomes, similar to the previously reported genomes [30].…”
Section: Discussionsupporting
confidence: 88%
“…The size of these cp genomes were almost similar with previously reported chloroplast genome of B . sacra (160,543 bp) [46], Azadirachta indica (160,737 bp) [47], Citrus sinensis (160,129 bp) [48] and Ailanthus altissima [49], which belong to order Sapindales. Both of these genomes possess the quadripartite structures comprises a pair of inverted repeats (IRa and IRb) separated by small single copy region (SSC) and large single copy region (LSC).…”
Section: Resultsmentioning
confidence: 99%